Excitotoxic superoxide production and neuronal death require both ionotropic and non-ionotropic NMDA receptor signaling. Issue 1 (December 2018) - Minnella, Angela; Zhao, Jerry; Jiang, Xiangning; Jakobsen, Emil; Lu, Fuxin; Wu, Long; El-Benna, Jamel; Gray, John; Swanson, Raymond
Abstract NMDA-type glutamate receptors (NMDAR) trigger superoxide production by neuronal NADPH oxidase-2 (NOX2), which if sustained leads to cell death. This process involves Ca2+ influx through NMDAR channels. By contrast, comparable Ca2+ influx by other routes does not induce NOX2 activation or cell death. This contrast has been attributed to site-specific effects of Ca2+ flux through NMDAR. Here we show instead that it stems from non-ionotropic signaling by NMDAR GluN2B subunits. To evaluate non-ionotropic effects, mouse cortical neurons were treated with NMDA together with 7-chlorokynurenate, L-689, 560, or MK-801, which block Ca2+ influx through NMDAR channels but not NMDA binding. NMDA-induced superoxide formation was prevented by the channel blockers, restored by concurrent Ca2+ influx through ionomycin or voltage-gated calcium channels, and not induced by the Ca2+ influx in the absence of NMDAR ligand binding. Neurons expressing either GluN2B subunits or chimeric GluN2A/GluN2B C-terminus subunits exhibited NMDA-induced superoxide production, whereas neurons expressing chimeric GluN2B/GluN2A C-terminus subunits did not. Neuronal NOX2 activation requires phosphoinositide 3-kinase (PI3K), and NMDA binding to NMDAR increased PI3K association with NMDA GluN2B subunits independent of Ca2+ influx. These findings identify a non-ionotropic signaling pathway that links NMDAR to NOX2 activation through the C-terminus domain of GluN2B.